In Search of Consensus on WTO Consensus Decision-Making - Van den Bossche, Peter (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional)

(untitled) (Société québécoise de droit international, 2025)
The World Trade Organization’s (WTO’s) reliance on consensus, once valued for inclusivity and legitimacy, has become a source of deep paralysis. Under this practice, any of the 166 Members can block a decision, as shown by the veto of India, Türkiye and South Africa of the decision on the inclusion in Annex 4 of the WTO Agreement of the 2024 Investment Facilitation for Development Agreement. Such obstruction, often driven by unrelated grievances, prevents over three-quarters of Members from advancing plurilateral initiatives and undermines even basic functions, such as appointing Appellate Body members. The article highlights how consensus is defended by many, particularly the ACP and African Groups, as a safeguard for smaller and vulnerable economies against power politics. They argue the consensus principle is “non-negotiable”. By contrast, the sponsors of the Singapore Communication, including the European Union and China, denounce the abuse of consensus and call for its reform. The “responsible consensus” proposal suggests that Members blocking consensus should justify this action, engage in dialogue, and accept differentiated commitments. Critics of this proposal, however, warn that “responsible” is a vague concept and risks altering the essence of WTO decision-making. This debate encapsulates a broader struggle: how to reconcile inclusivity with effectiveness. Preserving consensus without reform risks paralysis, but changing it raises fears of eroding equality among Members.